Burnout in athletes - Gustafsson, H.; Madigan, D. J.; Lundkvist, E. (Handbuch Stressregulation und Sport, 2017)
Although most athletes do from time to time experience symptoms of fatigue and exhaustion, they are probably never near more maladaptive states such as burnout. Being physically tired after a long training camp or feeling drained after a long season is normal for competitive athletes. After short recovery periods, the motivation for more training and new competitions quickly returns. However, a small number of athletes (1-2%) will experience a more serious and chronic state of exhaustion that eventually can lead to a total withdrawal from sport indicative of burnout. Among these are often the most ambitious and talented athletes which is problematic for talent development programs and a potential tragedy for the athlete (Gustafsson, Kenttä, Hassmén, and Lundqvist 2007). In this chapter we will give an overview of the athlete burnout literature. This includes a critical stance towards our current knowledge and how future research can increase our understanding of athlete burnout. Finally, we aim to present examples of how theory can inform practice, and we will make suggestions for prevention and treatment in order to help talented athletes avoid burnout symptoms and more severe forms of training maladaptation.